Claiming modernity through clothing: gender and education in Pakistani Muslim and Indian Hindu communities. Issue 2 (17th February 2019) - Khurshid, Ayesha; Shah, Payal
ABSTRACT: Through focusing on forms of clothing, this article reveals how educated women from marginalized communities in Pakistan and India made differential claims to being modern. Our analysis of two ethnographic studies shows how the participants mobilized their subjectivities as modern and educated women through a distinction between 'local modern' and 'local traditional'. In this article, our goal is not to define modernity, but instead to illuminate what it meant to be modern in both contexts. We integrate the narratives of young, rural Muslim women in Pakistan with those of young, rural Hindu women in India to disrupt the linear telling of the production of universal and homogenous modernity through education.